Multiphase soft magnetic BaFe2O4 hexagonal ferrite material as well as preparation method and application thereof
Through the method of ion doping and sintering temperature regulation, the resonance frequency and low-loss application frequency upper limit of multiphase soft magnetic BaFe2O4 hexagonal ferrite materials are improved, solving the application limitations of existing magnetic materials in high-frequency communication, and achieving wide application in the field of wireless communication in ultra-high frequency bands.
Patent Information
- Application Number
- CN202411771600.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-08
AI Technical Summary
The application of existing magnetic materials in high-frequency electromagnetic wireless communication is limited by frequency response and magnetic loss, and it is difficult to meet the communication needs of ultra-high frequency bands.
The multiphase soft magnetic BaFe2O4 hexagonal ferrite material is used to adjust the super-exchange integration and magnetocrystal anisotropy field of the material through ion doping and sintering temperature regulation, thereby improving the resonance frequency of the material and the upper limit of the application frequency of the low-loss application.
The resonance frequency of the material is adjusted to above 10 GHz, and the application frequency upper limit of low loss (tan δ < 0.1) reaches 5 GHz, meeting the wireless communication needs of ultra-high frequency bands.
Smart Images

Figure CN119786234A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ferrite materials, and in particular to a multi-phase soft magnetic BaFe 2 O 4 Hexagonal ferrite material, preparation method and application thereof. Background Art
[0002] As wireless communication has higher and higher requirements for communication capacity and communication speed, the operating frequency of devices used in wireless electronic devices has increased accordingly. The current main application frequency of 5G communication has reached 5 GHz, and the application frequency of antenna materials used in communication has increased accordingly. For electromagnetic waves to enter the antenna without reflection, it is necessary to achieve impedance matching between the antenna and the air, that is, the relative magnetic permeability and relative dielectric constant of the antenna material are equal. At present, the antenna materials studied in this field are mainly based on microwave dielectric ceramics and ferrite soft magnetic materials. Among them, microwave dielectric ceramics have a high dielectric constant and no magnetic permeability, and cannot achieve good impedance matching characteristics. In contrast, ferrite materials have a higher magnetic permeability, which can achieve iso-magnetic matching characteristics, effectively enhance the receiving efficiency of antenna materials, and reduce the transmission power of electromagnetic signals, thereby reducing energy loss and spatial electromagnetic noise pollution. At the same time, it can achieve device miniaturization and save space through a larger magnetic permeability and dielectric constant product factor.
[0003] However, the frequency response of magnetic materials is limited by the Snoek limit, that is, the product of the initial magnetic permeability and the resonant frequency of the material is proportional to the saturation magnetization of the material. When the magnetic resonance frequency is reached, the magnetic permeability of the material decreases significantly and the magnetic loss increases. Therefore, the application of magnetic materials in high-frequency electromagnetic wireless communications is subject to certain restrictions. For example, the upper limit of the resonant frequency of hexagonal soft ferrites (M, Y, Z types) with higher resonant frequencies is mostly concentrated in the range of 6-10 GHz, and the application frequency with magnetic loss less than 0.1 is even lower than 3 GHz.
[0004] In summary, a multiphase soft magnetic BaFe 2 O 4 Hexagonal ferrite materials and preparation methods thereof solve the above-mentioned technical problems arising in practical applications and are of great significance to wireless communications and other related fields. Summary of the invention
[0005] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a multi-phase soft magnetic BaFe 2 O 4 The preparation method of hexagonal ferrite material comprises the following steps: (1) Fe 2 O 3 、BaCO3 、Bi 2 O 3 、Co 3 O 4 The raw material is processed by wet ball milling, and then dried and sieved to obtain raw material powder; (2) The raw material powder is pre-calcined, the pre-calcined powder is ground and sieved, and then subjected to secondary wet ball milling. After completion, it is dried and sieved to obtain granulated powder; (3) adding a binder to the granulated powder and granulating it, and then preparing a green body; (4) The green body is sintered to obtain multiphase soft magnetic BaFe 2 O 4 Hexagonal ferrite material.
[0006] Preferably, in step (1), according to the multiphase soft magnetic BaFe 2 O 4 The chemical formula of hexagonal ferrite material is Ba 0.4- x Bi x Co 0.6 Fe 2 O 4 Prepare the corresponding proportion of Fe 2 O 3 、BaCO 3 、Bi 2 O 3 、Co 3 O 4 , 0<x<0.4.
[0007] Wet ball milling is a technology widely used in material processing, which improves grinding efficiency and product quality by adding liquid medium during the grinding process. Those skilled in the art can select a suitable solvent according to actual conditions. Among them, water and ethanol are widely available, have low pollution and are easy to post-process, and are suitable solvent selection types for the present invention. Water performs well in grinding aid, improving grinding efficiency, protecting liner, slurry uniformity, environmental protection and energy saving, while ethanol has advantages in reducing material viscosity, preventing agglomeration and cooling effect.
[0008] The appropriate material-liquid ratio and milling parameters in the ball milling process can ensure uniform mixing and effective grinding of the raw materials, thereby obtaining the desired product quality and performance. The appropriate ratio or parameters can also help reduce the ball milling time and improve production efficiency.
[0009] Preferably, in step (1), the solvent for wet ball milling includes at least one of water and ethanol.
[0010] Further preferably, in the wet ball milling, the mass ratio of the solvent to the raw material is 1-3:1.
[0011] Preferably, in step (1), the wet ball milling treatment time is 2-4 h and the rotation speed is 250-350 rpm.
[0012] Preferably, in step (2), the pre-calcination method comprises the following steps: heating to 900-1100°C at a rate of 1-5°C / min and keeping the temperature for 2-6 hours, and then naturally cooling to room temperature to obtain pre-calcined powder.
[0013] Preferably, in step (2), the solvent for the secondary wet ball milling includes at least one of water and ethanol.
[0014] Further preferably, in the secondary wet ball milling, the mass ratio of the solvent to the raw material is 1-3:1.
[0015] Preferably, in step (2), the wet ball milling treatment time is 3-10 h and the rotation speed is 250-350 rpm.
[0016] Those skilled in the art can use conventional processes to complete granulation, and process it into a green body of target specifications according to the element shape required for the application. The type and amount of the binder used in granulation are various. As shown in the embodiment of the present invention, PVA glue accounting for 10 wt.%-20 wt.% can be added to the granulation powder for granulation, and then the granules are pressed into a ring-shaped green body.
[0017] Preferably, in step (4), the sintering temperature is 1040-1120° C. and the sintering time is 6-10 h.
[0018] In a second aspect of the present invention, a multi-phase soft magnetic BaFe 2 O 4 The hexagonal ferrite material is made by the preparation method of the first aspect of the present invention.
[0019] In a third aspect of the present invention, there is provided a multiphase soft magnetic BaFe 2 O 4 The reference of hexagonal ferrite material is specifically its application as a magnetic material in the preparation of wireless communication components.
[0020] BaF 2 O 4Ferrite is an intermediate product in the process of forming hexagonal ferrite. Its saturation magnetization intensity approaches zero, showing a paramagnetic phase. However, some literature (K. Melzer, M. Lukasiak, B. Lippold, A. Martin, HYPERFINE FIELDS AND MAGNETIC PROPERTIES OF BARIUM MONOFERRITE, 1990.) shows that it exhibits antiferromagnetism at low temperatures, indicating that there is ferrimagnetic interaction inside the material, and it has the potential to develop excellent soft magnetic properties. At the same time, AB 2 O 4 The structure has two crystal structures, spinel and hexagonal. In soft magnetic materials, spinel structure is generally easier to form, showing high magnetic permeability. Therefore, BaFe 2 O 4 There is a lot of room for magnetic properties control. 2 O 4 As an impurity phase in BaM hexagonal ferrite, it will have a great influence on its high-frequency electromagnetic properties. 2 O 4 It is a soft magnetic material that can achieve high magnetic permeability at higher frequencies.
[0021] Based on the above phenomenon, in order to achieve a higher resonant frequency hexagonal ferrite material, the design concept and principle of the present invention is to use ions with different ionic radii to replace the Ba element, adjust the interlayer distance between the oxygen ion layer containing the Ba element and other oxygen ion layers, and change the Fe 3+ -O-Fe 3+ The super exchange integral is regulated by adjusting the inclination angle and spacing between them, thus reducing the reverse magnetic moment and achieving the electromagnetic parameters of the ferrimagnetic material. At the same time, this regulation will also lead to changes in the magnetocrystalline anisotropy energy inside the ferrite, thus achieving the magnetocrystalline anisotropy field regulation of the ferrite.
[0022] The present invention adopts Co 2+ / Bi 3+ ions replace Ba ions and react by traditional solid phase method to generate a chemical formula of Ba 0.4-x Bi x Co 0.6 Fe 2 O 4 (0<x<0.4) ferrite material. Ideally, a mixture of oxides configured in a certain proportion forms an oxide complex under high temperature, and its crystal phase structure is single and is the same substance. However, due to the uncontrollable movement and migration of ions under high temperature during high temperature sintering, they enter different lattice sites, thus forming different crystal phase structures. 2O 3 The characteristics of relatively low melting point and poor thermal stability make it decompose and volatilize during high-temperature sintering to form vacancies, change the distance between oxygen ion layers, and at the same time, the low melting point can form a liquid phase, which is helpful for sintering and promotes grain growth. Different temperatures will lead to different volatilization amounts. The volatilization of elements will cause some components to deviate from the designed components and form a second phase. The proportion of the two-phase structure, the degree of crystallization, and the grain size can be regulated by adjusting the ion doping ratio and the sintering temperature, thereby achieving the regulation of magnetic permeability and resonance frequency, showing different magnetic dispersion characteristics.
[0023] Thus, the present invention regulates the crystal phase structure of the material by ion doping and sintering temperature, and finally forms a dual-phase hexagonal crystal phase composite ferrite material. As presented in the specific implementation of the present invention, this method effectively adjusts the resonant frequency of the material to above 10 GHz, and the upper limit of the low loss (tan δ < 0.1) application frequency reaches 5 GHz.
[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a multiphase soft magnetic BaFe 2 O 4 The preparation method of the hexagonal ferrite material adopts a solid phase method for reaction, which has the advantages of simple process and convenience for large-scale production.
[0025] The present invention provides a multiphase soft magnetic BaFe 2 O 4 Hexagonal ferrite material improves the material's resonant frequency and upper limit of low-loss application frequency, and can meet the performance requirements of ultra-high frequency band applications.
[0026] The present invention provides a multiphase soft magnetic BaFe 2 O 4 The application of hexagonal ferrite materials, as magnetic materials, has broad application prospects in fields such as wireless communications. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the process flow of Example 1; Figure 2 The multiphase soft magnetic BaFe prepared in Example 1 2 O 4 X-ray diffraction (XRD) pattern of hexagonal ferrite material; Figure 3 The multiphase soft magnetic BaFe prepared in Example 1 2 O 4 Electromagnetic parameter curve of hexagonal ferrite material; Figure 4The multiphase soft magnetic BaFe prepared at different sintering temperatures in Example 4 2 O 4 Electromagnetic parameter curve of hexagonal ferrite material; Figure 5 The multiphase soft magnetic BaFe prepared at different doping amounts in Example 5 2 O 4 Electromagnetic parameter curve of hexagonal ferrite material. DETAILED DESCRIPTION
[0028] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0029] Example 1 A multiphase soft magnetic BaFe 2 O 4 The preparation method of hexagonal ferrite material, such as Figure 1 As shown, the steps are as follows: (1) According to Ba 0.3 Bi 0.1 Co 0.6 Fe 2 O 4 Prepare Fe 2 O 3 55.1 wt.%,BaCO 3 20.3 wt.%Co 3 O 4 16.6wt.%Bi 2 O 3 8.0wt%, and then directly put it into a ball mill; use deionized water as a solvent to pour into the ball mill to disperse the raw material powder, and the mass ratio of the raw material to deionized water is 1:2; ball milling for 2 hours, the ball mill speed is 250 rpm, and after ball milling, the material is discharged, dried and sieved to obtain the raw material powder; (2) The raw material powder is placed in a clean alumina crucible that has been calcined in advance, and then placed in a muffle furnace, and kept at 1000 °C for 4 h at a heating rate of 3 °C / min, and then cooled with the furnace to complete the pre-calcination treatment; the obtained pre-calcined powder is placed in a mortar and ground, and then the raw material is sieved, poured into a ball mill, and the same ball milling parameters are used for secondary wet ball milling for 4 h. After completion, the material is discharged, dried and sieved to obtain granulated powder; (3) adding 15% of the total weight of PVA glue to the granulated powder for granulation, and pressing the granules into a ring-shaped green embryo with a size of Φ8 mm×Φ3 mm×Φ3 mm; (4) The green body was sintered at 1040 °C for 6 h to obtain multiphase soft magnetic BaFe2 O 4 Hexagonal ferrite material.
[0030] Example 2 In this embodiment, X-ray diffraction was used to analyze the multiphase soft magnetic BaFe 2 O 4 Hexagonal ferrite materials were characterized, and the results are as follows Figure 2 As shown. Figure 2 It can be seen that its diffraction peak is similar to that of R-3m crystalline CoFe 2 O 4 (PDF #79-1744) and Ba 2 Co 2 Fe 12 O 22 (PDF#82-0472) The standard diffraction peaks are consistent, indicating that the multiphase soft magnetic BaFe 2 O 4 The hexagonal ferrite material sample is composed of these two hexagonal phases.
[0031] Example 3 For the application in antenna materials, its electromagnetic parameters are important measurement indicators, namely the dielectric constant and magnetic permeability of the material. For different electromagnetic frequency bands, different test methods will be used to implement electromagnetic parameter testing based on the electromagnetic characteristics of the material. Generally, in the microwave frequency band, the transmission-reflection method is often used to measure the electromagnetic parameters of the material.
[0032] The transmission reflection method generally uses electromagnetic signals of different frequencies to interact with the test material. The electromagnetic signal will be partially reflected at the interface between the material and the air, and partially transmitted through the material, thus obtaining a set of S parameters. The electromagnetic parameters of the material can then be solved in reverse through the wave equation. The electromagnetic parameter measurement system is mainly composed of a vector network analyzer, a coaxial cable, an APC 7mm connector, and a coaxial air line. The sample is installed at one end of the coaxial air line, and then the air line loaded with the sample is connected to the vector network analyzer through a coaxial cable. The vector network analyzer transmits electromagnetic signals and receives signals reflected from the sample surface and transmitted signals. After normalization, the S parameter curve is obtained. Finally, the electromagnetic parameter measurement software calculates the output material's dielectric constant and magnetic permeability curves as a function of frequency, as shown below. Figure 3 Sample curve shown.
[0033] Since the magnetization vector and polarization vector inside the material will respond to the external electromagnetic signal, forming an orientation arrangement, the magnetic field (electric field) will be enhanced externally, and the magnetic field (electric field) increment is measured by the magnetic permeability (dielectric constant). The level of magnetic permeability and dielectric constant indicates the strength of the material's ability to conduct dynamic electromagnetic fields. The higher the magnetic permeability and dielectric constant, the smaller the size of the electromagnetic wave can be transmitted, and the high magnetic permeability can form a good impedance matching characteristic with the dielectric constant, realizing the non-reflection reception and radiation of electromagnetic waves between multi-medium interfaces. As the direction of the external electromagnetic field changes, the magnetization vector (or polarization vector) flips accordingly. This flip response rate reflects the quality of the material's frequency response characteristics. When its flip rate cannot keep up with the rate of change of the external electromagnetic field, a resonant absorption phenomenon will occur, and the real part of the magnetic permeability (dielectric constant) will decrease significantly with the increase of frequency, and the magnetic (dielectric) loss will increase significantly. At this time, the material is no longer suitable for conducting electromagnetic waves. Therefore, there is an upper limit to the application frequency of magnetic materials, that is, the real part of the magnetic permeability decreases and the magnetic loss tangent increases to a frequency above 0.1.
[0034] Figure 3 is the electromagnetic parameter curve of the material, (a) and (b) are the curves of the change of the material's magnetic permeability with frequency. As the frequency increases, the material's magnetic permeability changes slightly, while the magnetic loss increases. In the range of 1-4 GHz, the growth is relatively slow, and the loss tangent value is less than 0.07. When the frequency increases to above 4 GHz, the magnetic loss increases, and at 5 GHz, the magnetic loss reaches more than 0.1. Figure 3 As shown in (a), the real part of the corresponding sample magnetic permeability remains at around 1.7 in the range of 1-6 GHz, with no obvious downward trend, showing a relatively broadband magnetic conductivity characteristic. Figure 3 (c) and (d) are the dielectric constant and dielectric loss of the material. Since there is no polarization resonance mechanism in the microwave frequency band, the dielectric constant basically does not change with frequency, and the loss increases slightly. The magnetic permeability, dielectric constant and loss at specific frequency points are shown in Table 1.
[0035] Table 1: Multiphase soft magnetic BaFe prepared in Example 1 2 O 4 Electromagnetic parameter values of hexagonal ferrite materials at a single frequency point in the range of 2-6 GHz
[0036] The above results show that the sample exhibits excellent electromagnetic parameters in the range of 2-5 GHz, with magnetic loss less than 0.1 and dielectric loss below 0.02.
[0037] Example 4 This example studies the Ba 0.4-x Bi x Co0.6 Fe 2 O 4 (x=0.1) Electromagnetic parameters of the sample. The preparation method of the sample in this embodiment is the same as that in embodiment 1, except that the sintering temperatures are adjusted to 1080°C and 1120°C respectively, and the multiphase soft magnetic BaFe 2 O 4 The hexagonal ferrite material and Example 1 were tested for electromagnetic parameters using the same testing method as Example 3. The results are as follows: Figure 4 shown.
[0038] Figure 4 This is the electromagnetic parameter curve of the sample sintered at different temperatures under the optimal doping amount. It can be seen from the figure that with the increase of temperature, the high-frequency magnetic permeability (f>4GHz) of the material shows a downward trend. Although the low-frequency magnetic permeability of the sample sintered at 1080 ℃ is almost the same as that at 1040 ℃, its loss increases, and the dielectric constant increases. It may be that the internal grain growth is too large, resulting in a decrease in resistivity, forming a certain eddy current loss, which has a negative effect on high-frequency performance. After the temperature rises to 1120 ℃, the magnetic permeability and dielectric constant decrease at the same time, and from the curve of the change of magnetic permeability with frequency, it can be seen that the magnetic resonance frequency moves to a low frequency, resulting in an increase in loss.
[0039] Example 5 This example studies the Ba doping with different doping amounts at 1040 °C. 0.4-x Bi x Co 0.6 Fe 2 O 4 (x=0.1, 0.125, 0.15, 0.175) Electromagnetic parameters of samples. The preparation method of the samples in this embodiment is the same as that in embodiment 1, except that the doping amount x is controlled to be 0.125, 0.15, and 0.175, respectively. 2 O 4 The hexagonal ferrite material and Example 1 were tested for electromagnetic parameters using the same testing method as Example 3. The results are as follows: Figure 5 shown.
[0040] Depend on Figure 5 It can be seen that with the increase of doping amount, the magnetic permeability of the material decreases, and the resonance frequency moves to low frequency, the loss increases, and the dielectric constant and loss increase at the same time. This may be because with the increase of Bi content, the sintering temperature of the material decreases. Sintering at 1040 ℃ will cause the grains to grow too large, the effective polarization vector increases, the dielectric constant increases, and the reduction in the number of grain boundaries will cause the resistivity of the material to decrease, increasing the leakage current loss.
[0041] In summary, the present invention uses ions with different ionic radii to replace the Ba element, adjusts the interlayer distance between the Ba-containing oxygen ion layer and other oxygen ion layers, and changes the Fe 3+ -O-Fe 3+ The super exchange integral is regulated by adjusting the inclination angle and spacing between the two materials, thereby reducing the reverse magnetic moment and realizing the electromagnetic parameters of the ferrimagnetic material. This regulation leads to the change of the magnetocrystalline anisotropy energy inside the ferrite, thus realizing the magnetocrystalline anisotropy field regulation of the ferrite. 2 O 3 It has the characteristics of low melting point and poor thermal stability. It decomposes and volatilizes at high temperature to form vacancies, changes the distance between oxygen ion layers, and then forms a liquid phase due to its low melting point, which helps sintering and promotes grain growth. By adjusting the ion doping ratio and sintering temperature, the composition ratio of the two-phase structure, the crystal integrity, and the grain size can be regulated, thereby achieving the regulation of magnetic permeability and resonant frequency, showing different magnetic dispersion characteristics, and finally obtaining a two-phase hexagonal crystal phase composite ferrite material, which effectively adjusts the resonant frequency of the material to above 10 GHz, and the low loss (tan δ<0.1) application frequency upper limit reaches 5 GHz, making it have broad application prospects in fields such as wireless communications.
[0042] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a multiphase soft magnetic BaFe2O4 hexagonal ferrite material, characterized in that: The steps include: (1) Fe2O3, BaCO3, Bi2O3, and Co3O4 are used as raw materials, and the raw materials are processed by wet ball milling, followed by drying and sieving to obtain raw material powders; (2) The raw material powder is pre-calcined, the pre-calcined powder is ground and sieved, and then subjected to secondary wet ball milling. After completion, it is dried and sieved to obtain granulated powder; (3) adding a binder to the granulated powder and granulating it, and then preparing a green body; (4) The green body is sintered to obtain a multiphase soft magnetic BaFe2O4 hexagonal ferrite material.
2. The method for preparing the multiphase soft magnetic BaFe2O4 hexagonal ferrite material according to claim 1, characterized in that: In the step (1), according to the chemical formula of the multiphase soft magnetic BaFe2O4 hexagonal ferrite material Ba 0.4-x Bi x Co 0.6 Fe2O4 prepares Fe2O3, BaCO3, Bi2O3, Co3O4 in corresponding proportions, 0<x<0.
4.
3. The method for preparing the multiphase soft magnetic BaFe2O4 hexagonal ferrite material according to claim 1, characterized in that: In the step (1), the solvent for wet ball milling includes at least one of water and ethanol; in the wet ball milling, the mass ratio of the solvent to the raw material is 1-3:
1.
4. The method for preparing the multiphase soft magnetic BaFe2O4 hexagonal ferrite material according to claim 1, characterized in that: In the step (1), the wet ball milling process is performed for 2-4 h at a rotation speed of 250-350 rpm.
5. The method for preparing the multiphase soft magnetic BaFe2O4 hexagonal ferrite material according to claim 1, characterized in that: In the step (2), the pre-sintering treatment method comprises the following steps: heating to 900-1100°C at a rate of 1-5°C / min and keeping the temperature for 2-6 hours, and then naturally cooling to room temperature to obtain pre-sintered powder.
6. The method for preparing the multiphase soft magnetic BaFe2O4 hexagonal ferrite material according to claim 1, characterized in that: In the step (2), the solvent of the secondary wet ball milling includes at least one of water and ethanol; in the secondary wet ball milling, the mass ratio of the solvent to the raw material is 1-3:
1.
7. The method for preparing the multiphase soft magnetic BaFe2O4 hexagonal ferrite material according to claim 1, characterized in that: In the step (2), the wet ball milling treatment time is 3-10 h, and the rotation speed is 250-350 rpm.
8. The method for preparing the multiphase soft magnetic BaFe2O4 hexagonal ferrite material according to claim 1, characterized in that: In the step (4), the sintering temperature is 1040-1120°C and the sintering time is 6-10 h.
9. A multiphase soft magnetic BaFe2O4 hexagonal ferrite material, characterized in that: The method is as described in any one of claims 1 to 8.
10. An application of the multi-phase soft magnetic BaFe2O4 hexagonal ferrite material as claimed in claim 9, characterized in that: Application as magnetic material in the preparation of wireless communication components.